Compositional design of single-phase rare-earth based high-entropy oxides (HEOs) by using the cluster-plus-glue atom model. Issue 5 (1st March 2023) - Spiridigliozzi, Luca; Ferone, Claudio; Cioffi, Raffaele; Dell'Agli, Gianfranco
Abstract: In the present study, we discuss a possible extension of our previously proposed empirical predictor for the formation of fluorite-structured High-Entropy Oxides (HEOs) based on equimolar mixtures of Rare-Earth (RE) Oxides. Indeed, by using the so-called cluster-plus-glue atom model, a very recently proposed theoretical model to describe the crystal structure of inorganic compounds, we were able to confirm the results of the standard deviation predictor, i.e. the relation between the formed phase(s) and the standard deviation of cationic radii, justifying them based on the phases' thermodynamic stability and the valency of the involved cations. At the same time, we propose an explanation of the role of Cerium and Zirconium in the formation of fluorite-structured HEOs, designing and predicting the behavior of a completely novel non-equimolar system (based on ZrO2, La2 O3 Yb2 O3, Sm2 O3, Gd2 O3 ), stabilized in a bixbyite-like single phase. Based on the presented results, we believe that a link between the geometrical aspects of the involved cations and their chemical-thermodynamic properties exists, providing a new tool to predict the behavior of systems in the intricate and intriguing world of High Entropy Oxides.